An autonomous redeployment algorithm for line barrier coverage of mobile sensor networks. (10th June 2014) - Jia, Jie; Wu, Xueli; Chen, Jian; Wang, Xingwei
Redistributing mobile sensor nodes to provide guaranteed barrier coverage is critical for many sensor networks applications, such as intrusion detection and border surveillance. In this paper, we study the problem of sensor redistribution in mobile sensor networks. We first give the formulation of the theoretical analysis on what is optimal sensor layout with the given random deployment. Then, we propose a fully distributed sensor redistribution algorithm to achieve line–based barrier coverage for mobile sensor networks. We formally prove that our algorithm can reach a final stable deployment and achieve barrier coverage in a finite time. Extensive simulations are conducted to verify the validity of our analysis for mobile sensor networks.